2021
DOI: 10.1111/1365-2664.13973
|View full text |Cite
|
Sign up to set email alerts
|

Tree species richness promotes an early increase of stand structural complexity in young subtropical plantations

Abstract: Forest plantations are established globally to provide multiple ecosystem services such as the production of timber, fuel and pulpwood (FAO, 2010). Specifically, global afforestation and reforestation efforts are among the major nature-based solutions employed to combat the adverse impacts of climate change. Currently, 168 Mha of degraded and deforested land, mainly located in the tropics and subtropics, has been pledged as restoration areas under the 'Bonn Challenge' (IUCN, 2020). A large part of this area is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 77 publications
(106 reference statements)
2
32
2
Order By: Relevance
“…We showed that the positive effects of tree diversity on wood productivity was strongly mediated by structural complexity within a stand: the higher the number of tree species in a plot, the greater the structural complexity and wood productivity of a forest stand. Although previous studies from tropical (18), subtropical (14), and temperate forests (17) using SSCI values derived from terrestrial laser scanning data have also demonstrated that tree species richness promotes structurally complex stands, our findings provide experimental evidence that variation in stand structural complexity acts as a central mechanism shaping BPRs in young tree communities. The greater structural complexity in mixtures also comes from the phenotypic plasticity of trees, as trees growing in species-rich neighbourhoods can adapt their crown morphology, both in size and shape, to maximise light capture, resulting in greater 13 crown complementarity and wood volume growth (5).…”
Section: Discussioncontrasting
confidence: 45%
See 4 more Smart Citations
“…We showed that the positive effects of tree diversity on wood productivity was strongly mediated by structural complexity within a stand: the higher the number of tree species in a plot, the greater the structural complexity and wood productivity of a forest stand. Although previous studies from tropical (18), subtropical (14), and temperate forests (17) using SSCI values derived from terrestrial laser scanning data have also demonstrated that tree species richness promotes structurally complex stands, our findings provide experimental evidence that variation in stand structural complexity acts as a central mechanism shaping BPRs in young tree communities. The greater structural complexity in mixtures also comes from the phenotypic plasticity of trees, as trees growing in species-rich neighbourhoods can adapt their crown morphology, both in size and shape, to maximise light capture, resulting in greater 13 crown complementarity and wood volume growth (5).…”
Section: Discussioncontrasting
confidence: 45%
“…The point cloud was converted to a voxel grid and then the ratio of the total number of filled voxels to the total number of voxels was quantified (58). We used a voxel size of 5 cm and a slice thickness of 25 cm following (14). SSCI consists of two components (Equation 1, Fig.…”
Section: Quantifying the Structural Complexity Of Tree Communitiesmentioning
confidence: 99%
See 3 more Smart Citations